Sources of debt-finance and CPSEs with high debt-equity ratio - Sharat Kumar (2016)
Companies in India, for long, have depended on bonds for both short-term and long-term loans. Recent years have seen introduction of new financial instruments in debt-finance that are more competitive and less cumbersome to avail. The Central Public Sector Enterprises (CPSEs) also need to take advantage of these developments. While the short-term borrowings of all the CPSEs put together stood at Rs. 2,18,804 crore, the long-term loans outstanding of all the CPSEs stood at Rs. 8,82,784 crore in 2014-15. The CPSEs, therefore, have a stake in debt-finance. They need to be prudent, however, in their borrowings taking cognizance of sustainability of debts. - Reproduced.
Keywords: Public sector